2005
DOI: 10.1111/j.1744-7429.2005.03148.x
|View full text |Cite
|
Sign up to set email alerts
|

Stilt Root Structure in the Neotropical Palms Iriartea deltoidea and Socratea exorrhiza1

Abstract: Many arborescent palms develop a stilt root cone that provides increased mechanical support on steep hillsides, better root aeration under waterlogged conditions, resprouting after mechanical damage, and rapid stem elongation. However, for most species the role of stilt roots is not well understood. We determined how palm size and slope inclination affected the structure of stilt roots in the neotropical palms Iriartea deltoidea and Socratea exorrhiza. We expected palm height to be lower on steep slopes becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…However, stilt root architecture did not differ between trees on sloped and flat locations. This supports previous work that S. exorrhiza alters neither its physical structure nor its investment in stilt roots in relation to degree of slope (Avalos et al 2005). The difference in stilt root height between La Selva and BCI may reflect site-specific abiotic conditions or population characteristics; however, it is unlikely that the difference (<0.3 m) on trees averaging over 14 m height is of biomechanical significance.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…However, stilt root architecture did not differ between trees on sloped and flat locations. This supports previous work that S. exorrhiza alters neither its physical structure nor its investment in stilt roots in relation to degree of slope (Avalos et al 2005). The difference in stilt root height between La Selva and BCI may reflect site-specific abiotic conditions or population characteristics; however, it is unlikely that the difference (<0.3 m) on trees averaging over 14 m height is of biomechanical significance.…”
Section: Discussionsupporting
confidence: 70%
“…The association of Iriarteoid palms with steep sloped habitats has led to the suggestion that stilt roots may be an adaptation to unstable conditions and provide mechanical stability against uprooting (Henderson 1990, Chiatante et al 2002. However, Avalos et al (2005) concluded that stilt roots do not provide enhanced stability on sloped locations, and found that stilt root architecture is instead a function of stem volume.In addition to hypotheses addressing enhanced structural stability, it has also been suggested that stilt roots allow for a unique vertical growth strategy. Hartshorn (1983) suggested that stilt roots in S. exorrhiza may facilitate rapid growth towards the canopy when light becomes available in the understory.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to our results, Kimura and Simbolon (2002) predicted that adult palms of Pinanga coronata should have a constant crown mass irrespective of stem height once the stem diameter has been fixed. Contrary to palms in which the stem diameter is fixed at an early stage, species like E. oleracea, E. precatoria and E. edulis, Prestoea decurrens, P. acuminata, Iriartea deltoidea and Socratea exorrhiza are able to exhibit a sustained increased in diameter with increasing stem height (Alves et al 2004;Avalos et al 2005;Avalos 2007;Avalos and Fernandez-Otarola 2010).…”
Section: Discussionmentioning
confidence: 95%
“…8 cm). It has been reported that some palm species including E. precatoria develop stilt roots to structurally support its slender-shaped stem [22,36]. Euterpe precatoria may need the large root portion accompanied by the stilt root development for support under physically unstable habitat conditions on sandy soils with seasonal inundation.…”
Section: Allometric Models For Estimating Root Massmentioning
confidence: 99%